(untitled) (Web of Teachers: Inderscience Research, 2025)
The main purpose of this article is to reveal and study the importance of sociolinguistic competence in improving the professional skills of foreign language teachers. Modern pedagogy requires teachers to form new skills. This article aims to reveal the role and importance of general competence and sociolinguistic competence in the professional skills of foreign language teachers.